An observational study using ultrasound to assess physiological changes following fluid bolus administration in paediatric sepsis in the emergency department. Issue 1 (December 2016) - Long, Elliot; Oakley, Ed; Babl, Franz; Duke, Trevor
Abstract Background Fluid bolus administration is widely recommended as part of the initial treatment of paediatric sepsis, though the physiological benefits and harms are unclear. The primary aim of this study is to determine the effect of fluid bolus administration on cardiac index (CI). Secondary aims are to determine the effect of fluid bolus administration on extra-vascular lung water (EVLW), whether fluid responsiveness can be predicted by inferior vena cava (IVC) collapsibility, and whether fluid responsiveness correlates with changes in vital signs. Methods/design A prospective observational study of children presenting to the Emergency Department of The Royal Children's Hospital with clinically diagnosed sepsis requiring fluid bolus administration. Prior to fluid bolus administration, an echocardiogram, lung ultrasound, and IVC ultrasound will be performed, and vital signs recorded. These will be repeated 5 min after and 60 min after fluid bolus administration. Recorded echocardiograms and lung/IVC ultrasound will be evaluated independently by a paediatric cardiologist and paediatric emergency physician, respectively, blinded to the patient identity and time of examination relative to time of fluid bolus administration. Fifty patients will be enrolled in the study based on a precision based sample size calculation. Results will be analysed for change in CI and change in EVLW 5 min after and 60 min after fluid bolus administration compared to baseline, IVC collapsibility as a predictor of fluid responsiveness, and the relationship between fluid responsiveness and changes in vital signs. Discussion This study will explore assumptions about the effect of fluid boluses on CI in children with sepsis, and will provide evidence for secondary effects on other organ systems. This may lead to novel methods for assessment and decision making in the initial resuscitation of paediatric sepsis in clinical and research settings, and will likely influence the design of future interventional studies in this arena. Trial registration The study is registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12614000824662; 04 August 2014).